Nulidad de sentencia ejecutoriada por omisión de solemnidades sustanciales en un juicio de prescripción extraordinaria de dominio - Castillo Ojeda, Ronald Stalin (2016)
In the ordinary trial No. 72-2012, analysis of our case study, developed in the Civil Court of El Oro based in the canton Zaruma, the judge avoca knowledge of the cause is the lawyer Richard Benitez Maldonado, in which the actor is Mr. Segundo Fernandez and Roberto Asanza defendants Asanza Maldonado and Carlos Manuel Zambrano Abelina by extraordinary acquisitive prescription domain. The purpose of the requirement is to acquire or extinguish any obligation, this acquisition or termination of rights will be consummated and perfected in the Civil Law; but not freed awareness of the situation that give rise prescription. So, what would become extinct in the Civil Law, will not be in conscience for the person whose favor is invoked. The aim of the research is to determine how it has complied with all the procedural formalities to apply for extraordinary acquisitive prescription domain of the property before the Civil Judge Canton Zaruma.